Motor fleet safety and security management - Della-Giustina, Daniel. (Taylor & Francis, 2012)
"Providing a thorough understanding of how to develop and manage a comprehensive motor fleet safety and instructional program, this newly updated edition presents the underlying concepts, basic techniques, and principles of motor fleet safety and security management. It addresses the critical steps for successful driver selection, training, instruction, and supervision. The comprehensive text also covers fleet safety program, accident prevention, small fleet considerations, vehicle inspection, organization of accident data, job safety analysis, fleet transportation publicity, school bus safety, hazardous material shipping and storage, and transportation security"--